Conformal Microfluidic-Blow-Spun 3D Photothermal Catalytic Spherical Evaporator for Omnidirectional Enhanced Solar Steam Generation and CO2 Reduction - Liu, Hao (John Wiley and Sons Inc, 2022)
10.1002/advs.202101232